1997
DOI: 10.1046/j.1365-3083.1997.d01-403.x
|View full text |Cite
|
Sign up to set email alerts
|

Instability of Natural Antibody Repertoires in Systemic Lupus Erythematosus Patients, Revealed by Multiparametric Analysis of Serum Antibody Reactivities

Abstract: Recent views on autoimmune diseases invoke generalized but specific perturbations in antibody repertoires, rather than the clonally restricted or non-specific polyclonal alterations proposed thus far. The present experiments analyse serum antibody reactivities in 24 systemic lupus erythematosus (SLE) patients and 17 healthy controls, using a method that quantitatively scores a large number of antibody reactivities and allows for multiparametric statistical analyses. The results show global but relatively speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…The natural B cell and T cell self-reactive repertoire is now recognized as the determinant for the homeostasis of lymphoid cells and the maintenance of self tolerance (33). Unstable patterns of antibody repertoires, possibly related to the adaptive immune response, have been described in systemic autoimmune diseases such as SLE (35). However, discriminant, stable, self-IgG patterns, probably related to pathogenic events, have been found in organ-specific autoimmune disease such as MS after 1 year of followup (30).…”
Section: Discussionmentioning
confidence: 99%
“…The natural B cell and T cell self-reactive repertoire is now recognized as the determinant for the homeostasis of lymphoid cells and the maintenance of self tolerance (33). Unstable patterns of antibody repertoires, possibly related to the adaptive immune response, have been described in systemic autoimmune diseases such as SLE (35). However, discriminant, stable, self-IgG patterns, probably related to pathogenic events, have been found in organ-specific autoimmune disease such as MS after 1 year of followup (30).…”
Section: Discussionmentioning
confidence: 99%
“…One of the most interesting is in autoimmune diseases, such as systemic lupus erythematosus 50 , atherosclerosis 51 , systemic sclerosis, and others.…”
Section: Omenn Syndromementioning
confidence: 99%
“…There is a fourth important aspect: Panama blots undergo significant and characteristic changes during severe alterations of immunological activities, such as human autoimmune diseases (41)(42)(43). More recently, changes in Panama blot profiles against autologous organs and/or E. coli extracts were correlated with clinical forms of chronic parasitic diseases, such as trypanosomiasis cruzi, malaria and schistosomiasis mansoni, both in humans and in mice (4,5,44).…”
Section: Panama Blotsmentioning
confidence: 99%
“…Aberrant patterns of connectivity of the immune system are associated with autoimmune diseases, in which significant changes in the pattern of immu-noglobulin formation occur (41)(42)(43). When von Pirquet and Schick characterized serum sickness , they showed that immunological activities, of themselves, are not always defensive and may be damaging to the organism (47).…”
Section: The Emergence Of Pathologymentioning
confidence: 99%
See 1 more Smart Citation